Świadectwo „tego, który widział” (J 19,34-35) - Witczyk, Henryk (Verbum Vitae, 2015)
The author of the present article is seeking to answer two questions: (1) Who is “the one who saw” and “bore witness” that from the pierced side of the crucified Jesus “came out water and blood” (John 19:34-35)? (2) What is the theological meaning of the reported witness? The author presents the arguments pointing to “the beloved disciple”, the ideal author of the Fourth Gospel, as the one who plays the role of the “witness” and “speaks truth”. The deepest message contained in his testimony regards the understanding of the death and resurrection of Christ. They signify the offering that, both to the “beloved disciple” and to all believers, is the source of Spirit (water), which in turn brings them Christ living in the filial relationship with the Father (blood), that is, Life.